The Influence of Education, Knowledge and Motivation (Literature Review) - Ahmadi Ahmadi; Hapzi Ali; Kasful Anwar (Dinasti International Journal of Management Science, 2023)
The Literature Review article on the Influence of Education, Knowledge and Motivation on Islamic Leadership is a scientific article that aims to build research hypotheses on the influence of variables to be used in further research, within the scope of Islamic Education Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Education has an effect on Islamic Leadership; 2) Knowledge influences Islamic Leadership; and 3) Motivation influences Islamic Leadership. Apart from these 3 exogenous variables that influence the endogenous variables of Islamic leadership, there are many other factors, including the variables of intelligence, communication and trust.